THE BEHAVIOR GENEROSITY MUHAMMADIYAH THROUGH LAZISMU IN MAKASSAR CITY (International Conference on Social and Islamic Studies, 2022)
The Muhammadiyah movement in generosity through LazisMu social philanthropy, to awaken the nature of generosity to everyone. LazisMu, can align themselves and contribute with other organizations, which can adapt to the current economic conditions due to the Covid-19 pandemic. This study aims to find out the technology-based LazisMu philanthropy model, and to know the concept of implementing LazisMu philanthropy which is known to the wider community. The type of research used is literature with qualitative descriptive methods, data collection techniques through primary and secondary, with content analysis. From the results of the study, it was found that: More intensive socialization about LazisMu philanthropy is needed, so that it is better known by Muhammadiyah residents and the wider community, Activate Muhammadiyah membership through electronic cards, so that it can become a culture of concern for Muhammadiyah residents in giving alms, giving infaq and so on. The use of the Cashless digital application, which makes non-cash transactions easier.  The result of the next idea is that it is necessary to add the LazisMu feature to the BSI application found in Mobile Banking or Internet Banking, so that generosity behavior for everyone becomes easy and effective, especially for Muhammadiyah residents.